A rare PALB2 germline variant causing G2/M cell cycle arrest is associated with isolated myelosarcoma in infancy. Issue 9 (12th August 2021) - Beer, Angelina; Beck, Ricardo; Schedel, Anne; von Bonin, Malte; Meinel, Jörn; Friedrich, Ulrike Anne; Menzel, Maria; Suttorp, Meinolf; Brenner, Sebastian; Fitze, Guido; Lange, Björn; Knöfler, Ralf; et al.
Abstract: Background: Isolated myelosarcoma of infancy is a rare presentation of acute myelogenous leukaemia (AML). Because of its rarity and early onset in infancy underlying genetic predisposition is potentially relevant in disease initiation. Methods and Results: We report an oncologic emergency in an infant with thoracic and intraspinal aleukaemic myeloid sarcoma causing acute myelon compression and lower leg palsy. Whole‐exome sequencing of the patient's germline DNA identified a rare PALB2 (OMIM 610355) variant (p.A1079S), which is located in a domain critical for the gene's proper function within the homology‐directed repair pathway. In line with potential DNA damage repair defects mediated by the PALB2 deregulation, the patient's fibroblasts showed increased sensitivity towards radiation and DNA intercalating agents. Conclusion: Therefore, we suggest PALB2 p.A1079S as a pathogenic variant potentially contributing to the here observed patient phenotype. Abstract : We present the finding of an infant with thoracic and intraspinal aleukemic myeloid sarcoma with a rare germline PALB2 variant (p.A1079S). The identified variant is located in a domain critical for the gene's proper function within the homology‐directed repair pathway. A functional role of the variant is further supported by increased sensitivity towards irradiation and DNA intercalating agents observed in primary cells from the patient carrying PALB2 p.A1079S.